Determining factors of intent for sustainability implementation: An exploratory study of family business successors - Dela Cruz, Paul John D. (Animo Repository, 2022)
Purpose – This study aims to dive into the minds of family business successors to identify factors that drive their intent to implement sustainable practices and introduce a framework that would best illustrate the emerging factors. Design/methodology/approach – This exploratory research incorporates the theory of planned behavior (Ajzen, 1985) as a conceptual model and grounded theory as the methodological approach (Glaser & Strauss, 1967) to determine the factors that influence the intent of family business successors to implement sustainable practices. Data was gathered by interviewing fifteen second-generation family business successors. Findings – Eight factors emerged that directly influence successors’ intent for sustainability implementation: Environment, Future Orientation, Business Improvement, Family Relations, Employees, Customers, Values and Mindset, and Community Development. Additionally, three moderating variables were also identified: Personal Resistance and Concerns, External Environmental Factors, and Financial Expense. Research limitations/implications – The study only extends to observable factors regarding the intent of successors to implement sustainable practices and does not consider whether participating respondents will implement such practices. The researchers also acknowledge that social desirability bias may have been present during the interview phase of the research. Additionally, the research is focused on proposing an emerging framework and utilizes a qualitative approach which leaves an opportunity for future research to validate and assign weights to the identified factors through quantitative means. Practical and social implications – Understanding the numerous factors that attribute to the implementation of sustainable practices is relevant to family businesses as it may serve as a guide on how these businesses would position themselves in the current economic and social landscape. Originality/value – This novel study provides a lens through which it assesses the role of successors in the implementation of sustainable business practices.